Meningkatkan Kreativitas UMKM dan Pendapatan Masyarakat melalui Penyuluhan Pemasaran Digital Produk Pisang Lumer - Lubis, Desy Irana Dewi; Siregar, Ade Rahma Ayu; Ramadhan, Burhan (Welfare : Jurnal Pengabdian Masyarakat, 2024)
The amount of crops circulating in this area has not been able to be utilized properly due to the lack of ideas in the community. Mayarakat wants to prosper their families through trade, but when they want to start, they are still reluctant and confused about what business to run because the trade circulation between sellers and buyers is only in that area. Utilizing crops in the form of bananas that will be processed to be more innovative fosters community enthusiasm for starting a business. This service is intended to form new MSMEs, increase community income, and introduce the community to digital marketing. As a result, the community understands better how to run a business in terms of processing income as capital that will be rotated back, the digital sales process, and good product packaging.